Effect of Treatments on the Iced storage Shelflife of Cuttlefish (Sepia aculeata) Fillets - P.M, Sherief; Joseph, Sophia Margaret (Fishery Technology, 2025)
Effect of dip treatments in 2% salt + 0.2% citric acid solution and in 0.01% butylated hydroxy anisole (BHA) solution, each for 10 minutes, on the biochemical and organoleptic quality of ice stored cuttlefish Sepia aculeata-Orbigny) fillets is reported. The salt + citric acid treatment was found to improve the appearance and overall quality of the fillets. Non protein nitrogen (NPN) and alpha amino nitrogen contents were higher in the salt+citric acid treated sample.The salt+citric acid treated sample was organoleptically in good condition for four days and fair upto six days of storage in ice. No discolouration was noticed in any of the samples during the period of storage.